The Role of Non-Financial Reporting in Modern Ecological Problems Updating and Solving - MYSAKA, Hanna; DERUN, Ivan; SKLIARUK, Iryna (Journal of Environmental Management and Tourism, 2021)
The relevance of the paper is due to the conscious demand of society for ecological results data of business against the background of climate change and ecological disasters. The purpose of the article is to develop recommendations aimed at improving informativeness and reliability of the companies’ non-financial reporting on their ecological management. The study is based on a legitimacy and legality analysis of the global practice of compiling and submitting non-financial reporting. It is determined that the Global Reporting Initiative (GRI) Standards are the most popular among the public-interest entities for the preparation of non-financial reporting. The authors have structured a set of current GRI Standards 300 series (Environmental topics) on the issues’ content. The authors have formed practical proposals increasing the informativeness of non-financial reporting, which is made according to the GRI Standards by identifying the need for additional data disclosure about the company’s policies on resource consumption, environmental protection, hazardous emissions and waste management. These proposals will help increase the credibility of non-financial reporting indicators by providing cross-sectional information on the same phenomenon or event in case of the absence of independent control over the statement’s reliability. It will be an important argument in favour of non-financial reporting as a data source for all stakeholders’ decision-making.